THE ABUNDANCE OF 13C IN MARINE ORGANIC MATTER AND ISOTOPIC FRACTIONATION IN THE GLOBAL BIOGEOCHEMICAL CYCLE OF CARBON DURING THE PAST 800 MA - Hayes J.M.; Strauss H.; Kaufman A.J. (My University, 1999)
New records of the abundance of 13C in marine organic matter have been compiled for (i) the later Neoproterozoic, from 800 to 543 Ma (346 analyses), (ii) the Cambrian through the Jurassic (1616 analyses), and (iii) the Cretaceous and Cenozoic (2493 analyses). Comparison of these to existing compilations of the abundance of 13C in sedimentary carbonates has allowed development of a record of the isotopic fractionation (=#TOC) accompanying the production and burial of organic material. Over time, globally averaged values of #TOC have fallen in three ranges: (i) greater than 32%% and apparently indicative of significant inputs from sulfide-oxidizing or other chemoautotrophic bacteria, notably during late Proterozoic interglacials at 752, 740-732, and 623-600 Ma; (ii) between 28 and 32%% and indicative of maximal fractionation of carbon isotopes by phytoplanktonic producers, during the Neoproterozoic from 800 to 750 and from 685 to 625 Ma and during the Phanerozoic up to the early Oligocene; and (iii) less than 28%%, probably reflecting a reduction of primary fractionation by some combination of low levels of CO2, rapid rates of growth, and high ratios of cellular volume to surface area during Neoproterozoic glaciations (740, 720, and 575 Ma) and since the early Oligocene. Evidence of similar variations during the Ordovician and Gondwanan glaciations is absent. The decline in #TOC since the early Oligocene, from 30 to 22%%, has been nearly linear. The structure of the record of #TOC suggests that the maximal isotopic fractionation between dissolved CO2 and primary biomass has consistently been 25%%. Overall, the records provide compelling evidence that values of #TOC have varied widely and that the long-term average fractionation is roughly 30%%.
Keywords: MARINE ORGANIC MATTER; ISOTOPIC FRACTIONATION; 800 MA